Perspectives of male mental health service users on their community integration following participation in a residential-based rehabilitation programme - Gamieldien, Fadia (Department of Health and Rehabilitation Sciences, 2015)
Current re-engineering of primary mental health care in South Africa is directed towards providing a continuum of care for people with serious mental disorders in order to relieve the cost and resource burden of longterm hospitalisation. In the Western Cape, Healthcare 2030 has been adopted as the guiding vision for health system reform. Residential-based rehabilitation programmes have been introduced to assist mental health service users to improve their functioning in occupations of daily life so that they are better equipped to cope with community living. Problem: There is limited South African occupational therapy research into male mental health service users' perspectives on the contribution that residential-based rehabilitation programmes makes to their community integration, despite the high numbers of males using the service. Purpose: To inform public mental health services on the contribution of a residential-based rehabilitation programme to the community integration of men with serious mental disorders. Research question: How does participation in a residential-based rehabilitation programme contribute to the community integration of men with serious mental disorders? Objectives of the study: To identify what men with serious mental disorders consider community integration to be, and to describe the key elements within the residential-based rehabilitation programme that influenced their community integration. Research design and methodology: An instrumental case study design was used to guide the research methodology and five male participants were identified through purposive sampling. Observations, semi-structured interviews, community maps and document analysis w ere used as data collection tools. Data was audio-recorded and transcribed f or inductive and thematic cross-case analysis. Ethical principles of beneficence, autonomy and non-maleficence were upheld throughout the research process. Findings: One theme and three categories emerged in the findings. The theme, 'It's a catch-22 situation', comprises three categories, namely: 'It's not just what you call it'; 'There's no one size for all'; and 'It's tricky choosing between places to go and things to do'. Conclusion: Male mental health service users who participate in a residential-based rehabilitation programme will be better prepared for community integration if they are involved in co-constructing their recovery plan so that it is more personalised.